Prospective observational study to evaluate the efficacy of labetalol versus nifedipine in the management of preeclampsia - D., Sarulatha; M., Menaga (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hypertensive disorders of pregnancy are the common medical disorders in pregnancy. It has effects both on expectant mother and fetus. Pre-eclampsia is a pregnancy specific multisystem disorder of unknown etiology, and accounts for 12-18% of maternal mortality. There is general consensus that maternal risk is decreased by antihypertensive treatment that lowers very high blood pressure. Objective of this study was to study the efficacy of oral labetalol versus oral Nifedipine in the management of preeclampsia in the antepartum and intrapartum period. Methods: The present study was conducted in a tertiary care centre, Chennai from October 2013 to September 2014. It was a prospective observational study done in antenatal ward and labor ward. All antenatal women diagnosed to have pre-eclampsia, irrespective of gestation are included in this study. Results: Age distribution of PIH patients and the maximum number of patients were 20-25 years of age. maximum patients of severe preeclampsia were primigravida. Both systolic and diastolic BP in the two groups (oral labetalol and oral Nifedipine groups) were not statistically significant as the p value is >0.005. Conclusions: From this study, authors found that both oral labetalol and oral nifedipine are effective and well tolerated when used for rapid control of blood pressure in severe hypertension of pregnancy.